The Use of Film Media in Arabic Language Learning at MA Al-UMM Malang - Harsono, Iwan; Al Anshory, Abdul Muntaqim (Maharaat: Jurnal Pendidikan Bahasa Arab, 2024)
Film media in Arabic language learning can transform classroom dynamics, making them more interactive, engaging, and enjoyable, and can alleviate student boredom. This research aims to explain the use of film media in Arabic language learning. This research employed a descriptive qualitative research approach, that utilizes a natural setting to interpret occurring phenomena and conducts this through various existing methods. The research findings indicate that the use of film media in Arabic language learning at MA Al UMM Malang has a significant positive impact on the teaching and learning process. First, films have successfully broadened students' knowledge of multimedia technology, making learning more engaging and relevant to current developments. Second, learning time becomes more effective and efficient since films convey material concisely and clearly. Third, students' listening skills are improved by listening to film dialogue, which improve pronunciation and understanding of Arabic context. Fourth, students' speaking skills have been developed through discussions and role-plays after watching the films. Fifth, students' writing skills were strengthened by writing assignments for film reviews or summaries. Finally, students' reading skills are also improved with the provided film-related texts. Overall, film media has enriched students' learning experiences and improved their overall Arabic language competence.